Accounting for interest by real estate developers - Zimmer, Ian (Journal of Accounting and Economics, 1986)
This paper investigates accounting for interest by Australian real estate developers. It argues that management's choice of accounting technique is the result of ex ante contracting to prevent management opportunistic behavior, rather than a manifestation of opportunistic behavior per se. The argument provides a richer description of accounting choice and explains why, in Australia, leverage and the accounting method choice are correlated in the absence of bond covenants. The argument also explains why, inconsistent with political cost arguments, larger firms are more likely to capitalize than expense interest.